Histone H3K9 and H3K27 methylation regulates fungal alkaloid biosynthesis in a fungal endophyte–plant symbiosis. Issue 2 (17th March 2014) - Chujo, Tetsuya; Scott, Barry
Summary E pichloё festucae is a filamentous fungus that forms a mutually beneficial symbiotic association with Lolium perenne. This endophyte synthesizes bioprotective lolitrems (ltm) and ergot alkaloids (eas) in planta but the mechanisms regulating expression of the corresponding subtelomeric gene clusters are not known. We show here that the status of histone H3 lysine 9 and lysine 27 trimethylation (H3K9me3/H3K27me3) at these alkaloid gene loci are critical determinants of transcriptional activity. Using ChIP‐qPCR we found that levels of H3K9me3 and H3K27me3 were reduced at these loci in plant infected tissue compared to axenic culture. Deletion of E. festucae genes encoding the H3K9‐ (ClrD) or H3K27‐ (EzhB) methyltransferases led to derepression of ltm and eas gene expression under non‐symbiotic culture conditions and a further enhancement of expression in the double deletion mutant. These changes in gene expression were matched by corresponding reductions in H3K9me3 and H3K27me3 marks. Both methyltransferases are also important for the symbiotic interaction between E. festucae and L. perenne. Our results show that the state of H3K9 and H3K27 trimethylation of E. festucae chromatin is an important regulatory layer controlling symbiosis‐specific expression of alkaloid bioprotective metabolites and the ability of this symbiont to form a mutualistic interaction with its host.